Graphene-based quantum electronics - Dragoman, M.; Dragoman, D. (Progress in quantum electronics, 2009)
Graphene, which was discovered in 2004, is one of the most recent nanomaterials. Its uncommon physical properties and its potential applications in the area of quantum electronics have attracted a lot of attention. Graphene consists of a 0.34-nm-thick monolayer sheet of graphite consisting of carbon atoms in the sp 2 hybridization state, in which each atom is covalently bonded to three others. Graphene forms the basic structure of other carbon-based materials: when it is stacked it generates the graphite, when it is wrapped it creates carbon buckyballs, while when it is rolled-up it forms the carbon nanotube, which is a key material for nanoelectronic devices that working from few hundred megahertz up to X-rays. Graphene is the strongest material, having a Young modulus of about 2 TPa, and is the material with the highest mobility, due to its intrinsic ballistic transport. Graphene and carbon nanotubes can be easily functionalized by an applied voltage or pressure, or by chemical absorption of many molecules, such as oxygen or hydrogen. A functionalized graphene or carbon nanotube represents a bandgap-engineering material, which is the key concept in quantum electronics. Based on the above properties, many innovative quantum electronic devices can be built that can enhance research areas such as nanophotonics, nanoelectronics, or terahertz devices.